Job Vacancy Information System Based on SMS Gateway as Part of Tracer Study Alumni of UPI Cibiru Campus - Fahmi Candra Permana; Sisilia Sylviani; Feri Hidayatullah Firmansyah; Intan Permata Sari (Indonesia Journal on Computing (Indo-JC), 2022)
The waiting period for graduates of an educational institution to get a job can be a benchmark for the quality of the institution in carrying out the educational process for its graduates. One thing that indicates the success of the educational process in an institution is the absorption of graduates from that institution in the world of work. To achieve this, an educational institution requires a system that can provide services and specific attention to its graduates in obtaining information related to work by their scientific fields quickly and sustainably. In this paper, an information system based on SMS Gateway technology is designed as a medium that can provide information directly to graduates rapidly and sustainably according to the needs of graduates. The method that we used in this research is the Rapid Application Development method as an information system design method, and Black Box Testing as a test of information system applications that have been developed. This system was built as part of the Tracer Study for alumni of the UPI Cibiru Campus, to provide information on job vacancies by the scientific fields of its graduates.